MENGEMBANGKAN JIWA KEAGAMAAN ANAK (Perspektif Pendidikan Islam dan Perkembangan Anak Usia Dini) - Triana Rosalina Noor (Kuttab : Jurnal Ilmu Pendidikan Islam, 2020)
The first five years of development are a very important period in child development, because in this range, children experience optimal cognitive development. At that time, it became the right range to develop a child's religious spirit. The research method used is literature study, namely conducting a process of reviewing books, existing theories to be linked with the topic of developing the religious spirit of early childhood. The results of this study indicate that in the process of developing the religious and moral spirit of early childhood, they must consider the stages of children's development, both psychological and physical development. The development of a religious spirit can be carried out in a tangible form through participation in daily religious activities, so that children get firsthand real experiences taught by parents or teachers. Methods of delivery can be through lectures, games, stories, role playing, habituation and exemplary. Therefore, both parents and teachers need to provide stimulation so that their children can respond quickly to learning religious concepts in the hope that they can develop their sense of diversity.